Psikhoregulyatsiya v sporte - Smoletseva, V. N. (Teorija i Praktika fiziceskoj Kul'tury, 2001)
Psychoregulation is examining in two aspects: 1) as the ability of an athlete to operate the ideas, feelings, actions; 2) as the activity of an athlete on use of resources of psychoregulation in training and competitive activitywhich helps him (her) to display the optimum of his (her) own physical and technical abilities. The realization of long-term experimental researches has allowed to determine the state of the problem of psychoregulation in sports; to reveal the undeveloped questions of this problem; to determine the place and contents of psychoregulation in the structure of sports activity; to study its abilities in the increasing of the efficiency of sports activity; to develop the technique of mastering by the bases of psychoregulation of athletes in any specialization; to develop the techniques of its development for the concrete kinds of sports; to plan the ways of the further researches of the examined problem.